Digital Leadership A New Leadership Style for the 21st Century - Franco, Mario (IntechOpen, 2020)
Digital leadership has been seen as a phenomenon allowing competitive advantages for organizations, but some studies do not include the risks, benefits, and challenges of this type of leadership. Consequently, the objective of this book is to fill this gap by combining several studies from different perspectives. The various chapters presented here follow several approaches and applications that researchers explore in different contexts. This book intends therefore to add to the body of knowledge in leadership and digital areas. On the other hand, this work shows how digital leadership can stimulate organizational development in various countries and regions worldwide.